Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) Pada Masa Pandemi Covid-19 dan Pemberian Sembako Bagi Anak-Anak di Panti Asuhan Al-Hidayah Mataram - Siti Hidayatul Jumaah; Siti Yulianah M. Yusuf; Iswan Iswan; Johan Mashuri; Vidya Yanti Utami (Indonesian Journal Publisher, 2022)
Covid-19 has infected many people around the world, even causing death for sufferers. Children are a group that is vulnerable to the spread of Covid-19, especially children who live side by side like in orphanages. This activity aims to educate and assist children at the Al-Hidayah Orphanage in Mataram in implementing Clean and Healthy Living Behavior (PHBS) in order to avoid the transmission of Covid-19. This activity also received high enthusiasm, as seen from the active participation of participants in giving and answering questions. The educational materials for PHBS in preventing COVID-19 were given, namely Clean and Healthy Behavior in Schools, Introduction of COVID-19 and its symptoms, how to wash hands properly and correctly, how to apply cough etiquette, and how to maintain personal hygiene. It can be concluded that this activity succeeded in increasing children's knowledge in implementing clean and healthy living behavior in the school environment, especially in the Al-Hidayah Orphanage Mataram. assistance to those affected by the COVID-19 pandemic.